From sign to design: The role of domain transfer in redefining architecture locality (ARTEKS : Jurnal Teknik Arsitektur, 2025)
This research examines the design process using conceptual frameworks based on domain transfer to suggest a new model for architecture based on local contexts. Plowright's conceptual framework is a way of developing new ideas, in which architecture may or may not be subverted with concepts that are significant; meanings may also be redefined with ‘big ideas’ (concepts), analogy, metaphor or significant questions from inside and outside the realms of architecture. This research utilizes case study method through design and reflects on the design process within the context of the West Java Cultural Center design competition. This analysis deconstructed and explained the design process using the conceptual framework, identifying unique representations of cross-cultural and West Java culture as the basis for an architectural program. The case was used to understand the transformational architectural syntax occurring from local signs and symbols as evidence of innovation. The results of the case study fell within three areas: concepts as a way to achieve a place of innovation (hypothesis), transferring ideas based on locality into elements and syntax (transfer), and bringing them all together into a coherent design (coherence). Domain transfer was redefined in this case study as the translation of symbolic values and cultural attributes from non-architecture into architectural form and elements in pursuit of contextual design innovation.
Keywords: Concept; Culture; Design; Locality